Element Specific Monolayer Depth Profiling. (8th August 2014) - Macke, Sebastian; Radi, Abdullah; Hamann‐Borrero, Jorge E.; Verna, Adriano; Bluschke, Martin; Brück, Sebastian; Goering, Eberhard; Sutarto, Ronny; He, Feizhou; Cristiani, Georg; Wu, Meng; Benckiser, Eva; et al.
<x xml:space="preserve">Abstract</x> The electronic phase behavior and functionality of interfaces and surfaces in complex materials are strongly correlated to chemical composition profiles, stoichiometry and intermixing. Here a novel analysis scheme for resonant X‐ray reflectivity maps is introduced to determine such profiles, which is element specific and non‐destructive, and which exhibits atomic‐layer resolution and a probing depth of hundreds of nanometers. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>